2007
DOI: 10.3846/13923730.2007.9636452
|View full text |Cite
|
Sign up to set email alerts
|

Cracking and Strength of Reinforced Concrete Structures in Flexure Strengthened With Carbon Fibre Laminates

Abstract: The article presents the analysis of the cracking moment and the strength of beams reinforced with external carbon fibre. Experimental research of beams strengthened in this way has been carried out. Three different methods of anchoring external reinforcement were applied to strengthen the beams. The influence of anchorage on the cracking moment and the strength of the beams has been defined. Design methods for defining the cracking moment and the strength have been presented. The design procedure for defining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…R/C members resist bending moment using several mechanisms. Experimental investigations to predict the flexural strength of R/C members have been carried out by several researchers and several empirical formulas [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], based on experimental results, have been developed, Some of these formulas are used in prominent design codes such as the American Concrete Institute (ACI 440 R2) [6]. These formulas are used to predict the bending moment of concrete beams strengthen by CFRP, carry two point load as shown in figure (2) and they are functions of several flexural parameters.…”
Section: Ultimate Flexural Strength Of Rc Beams Strengthened By Cfrpmentioning
confidence: 99%
“…R/C members resist bending moment using several mechanisms. Experimental investigations to predict the flexural strength of R/C members have been carried out by several researchers and several empirical formulas [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], based on experimental results, have been developed, Some of these formulas are used in prominent design codes such as the American Concrete Institute (ACI 440 R2) [6]. These formulas are used to predict the bending moment of concrete beams strengthen by CFRP, carry two point load as shown in figure (2) and they are functions of several flexural parameters.…”
Section: Ultimate Flexural Strength Of Rc Beams Strengthened By Cfrpmentioning
confidence: 99%
“…Carbon fibers are widely used for dispersion reinforcement of conventional concrete in civil engineering to improve its mechanical properties and to prevent the formation of cracks due to deformation (Ferrari et al 2013;Qazi et al 2015;Tabatabaei et al 2014;Valivonis, Skuturna 2007;Wang, Adeli 2014). In the refractory castables, such fibers are not used because their operating temperature does not exceed 300-400 °C.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many researches [5][6][7][8][9][10][11] have been conducted to investigate the mechanical properties of the retrofitted members externally bonded with CFRP. It can be concluded that the bonding of the CFRP plates has a significant effect on enhancing the overall performance even for plates with a relatively low modulus of elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…The strengthening technology externally bonded with CFRP can considerably increase the strength at bending, reduce the deflections as well as crack width in area of tension, and also change the mechanical behavior and failure pattern during service. The researches [5,[8][9][10] demonstrated that the cracking moment in reinforced concrete beams with CFRP can significantly increase by 218%, from 12% to 230%. They also found that in strengthened flexural members, cracks are seen in bigger numbers and closer to each other; however, they are narrower than in beams without strengthened reinforcement.…”
Section: Introductionmentioning
confidence: 99%